The performance of sago starch and modified starch (FL-7 plus)in the KCl-starch mud system - Ismail, Issham; Chuah, Cheun Seong (COSTAM, 2001)
The readily available of local starch together with the many possibilities as to chemical modification constitute the basis for the great versatility of starch derivatives. An experiment was conducted on sago starch and modified starch (hydroxypropyl starch), used as fluid loss control additive in the KCI mud systems, which comprised of the study of the stability of the blended mud system with contaminants in the wellbore, such as formation water during drilling operation and also the thermal stability of the mud system. Consequently, the desired functions of the mud were stunted. Contamination tests were performed at temperature and pressure of 2500F and 500 psi respectively, to evaluate the ability of the mud to be safely used under the field condition. Nevertheless, the experimental results revealed that the modified starch gave better performance despite the presence of contaminants and high temperature compared to sago starch, which was sensitive to the Ca++ contamination and high temperature, in terms of filtration and rheological properties.